Unintended consequences eaudiobook - Woods, Stuart (Stone Barrington, 2016)
Stone Barrington is no stranger to schemes and deceptions of all stripes—as an attorney for the premier white-shoe law firm Woodman & Weld, he's seen more than his share. But when he travels to Europe under highly unusual circumstances, Stone finds himself at the center of a mystery that is, even by his standards, most peculiar. Two unexpected invitations may be the first clues in an intricate puzzle Stone must unravel to learn the truth...a puzzle that will lead him deep into the rarefied world of European ultrawealth and privilege, where billionaires rub elbows with spooks, insider knowledge is traded at a high premium, and murder is never too high a price to pay for a desired end. It soon becomes clear that beneath the bright lights of Europe lurks a shadowy underworld...and its only rule is deadly ambition.